Differences and Correlations of Anxiety, Sleep Quality, and Pressure-Pain Threshold between Patients with Chronic Low Back Pain and Asymptomatic People - Changming Xu; Zhiwei Fu; Juan Wang; Bao Wu; Xue-Qiang Wang (Pain Research and Management)
Background. Chronic low back pain (CLBP) is a clinically common and expensive disease. Patients frequently take sick leaves because of pain and dysfunction, and their unpleasant life and work experiences cause psychological depression and anxiety and affect their quality of life. Sleep disturbance is a common problem among patients with low back pain (LBP) with more than 50% complaining about poor sleep quality. This study aimed to explore the correlations between anxiety, sleep quality, and pressure-pain threshold (PPT) and their differences between patients with CLBP and asymptomatic people. Methods. Forty patients with CLBP and 40 asymptomatic people were recruited. Relevant data, including State-Trait Anxiety Inventory, Pittsburgh Sleep Quality Index, and PPT, were individually and independently collected by blinded physiotherapists with a practicing certificate and then statistically analyzed. An independent sample t-test was used to determine the intergroup differences between patients with CLBP and asymptomatic populations. Pearson correlation coefficient was employed for correlation analysis. Results. The CLBP group had significantly higher anxiety scores (41.64 ± 9.88 vs. 36.69 ± 8.31; t = −2.496, p=0.015) than the asymptomatic group. A significant difference was found in the total score of the Pittsburgh Sleep Quality Index (6.41 ± 2.43 vs. 5.09 ± 2.18; t = −2.628, p=0.010) but not in the trait anxiety (44.00 ± 7.83 vs. 42.67 ± 9.51; t = −0.695, p=0.489) of the two groups. State−Trait Anxiety Inventory showed a low to moderate negative correlation with PPT. No remarkable correlation was observed between Pittsburgh Sleep Quality Index and PPT. Conclusions. Patients with CLBP showed considerably worse state anxiety and sleep quality than asymptomatic people; however, no substantial difference in PPT was found between the two groups. The results suggest that in clinical practice, the focus should include pain and related social and psychological factors. CLBP treatment could be considered from multiple perspectives and disciplines.This trial is registered with Chinese Clinical Trial Registry (Trial registration: ChiCTR-TRC-13003701).